Pemikiran Ibnu Khaldun tentang Perdagangan dan Mekanisme Pasar Menuju Dinamika Ekonomi Modern - Johan Dwi Sutikno; Muhamad Aqim Adlan; Muhammad Aswad (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
This study examines Ibn Khaldun's thoughts on trade mechanisms and the concept of conventional economic markets, which tend to be exploitative, along with their impact on social injustice. According to Ibn Khaldun, alternative solutions exist, emphasizing that market and trade activities should focus on societal welfare, not just personal gain. This article analyzes the relevance of Ibn Khaldun's thoughts in Islamic economic theory concerning trade and markets amidst current economic dynamics. The methodology used is a qualitative approach, based on literature studies and empirical data. The results show that Ibn Khaldun's economic thoughts and theories, proposed six centuries ago, remain highly relevant. His concepts highlight the importance of providing necessities in remote areas, paying attention to the quality of education, and prohibiting monopolistic practices and transactions involving usury and opacity. These findings are expected to provide alternative solutions for governments facing increasingly complex economic challenges and encourage positive market mechanisms and global trade changes.